WEB-BASED MATERIALS FOR EXTENSIVE READING TO PROMOTE STUDENTS’ READING HABIT - Afi Ni'amah; Yunita Puspita Sari (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2016)
Alongwiththedevelopmentoftechnology,internethasbeencommonlyused inthelearningprocesstoincrease interestinlearning.WebQuestisanInternet-based learningmodelthatisproblem-basedlearningorientedinwhichthe studentsinteract directlywithlearningresourcesviatheInternet.LearningactivitiesthatuseWebQuest is a teaching  strategyusedin  Literal  Reading  Courseaimedat improving  students’ reading  skills. Employinganactionresearch, thestudyshowedthat  the materials providedinWebQuestwerenotonlyabletotrainstudentstocomprehendthecontent ofreading,butalsoprovideexposure tothe cultureofthe targetlanguage.Worksheets withproperinstructions  werefoundasadeterminantofthesuccessofthestrategyimplementationinimprovingthereadingskillsofstudents